The big free-tailed bat, Nyctinomops macrotis (Gray, 1839), in central America [El murciélago grande de cola libre, Nyctinomops macrotis (Gray, 1839), en Centro América] - Mora, José Manuel (2016)
The big free-tailed bat, Nyctinomops macrotis, is a large molossid with a discontinuous distribution in the southwestern United States and most of Mexico (northern range), and northern South America (southern range). In addition, the species has been documented in the Caribbean in Cuba (type locality), Hispaniola, and Jamaica. A large gap in the species distribution existed from the Isthmus of Tehuantepec (Mexico) southwardto southeast of the Darién Gap, between Panama and Colombia, an overland distance of some 2500 km. Here,we report the first records of the species for Central America, based on two recently collected specimens fromthe southern highlands of Honduras.